2005
DOI: 10.1016/j.pain.2004.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal procedural pain exposure predicts lower cortisol and behavioral reactivity in preterm infants in the NICU

Abstract: Data from animal models indicate that neonatal stress or pain can permanently alter subsequent behavioral and/or physiological reactivity to stressors. However, cumulative effects of pain related to acute procedures in the neonatal intensive care unit (NICU) on later stress and/or pain reactivity has received limited attention. The objective of this study is to examine relationships between prior neonatal pain exposure (number of skin breaking procedures), and subsequent stress and pain reactivity in preterm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
254
1
16

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 336 publications
(281 citation statements)
references
References 42 publications
(50 reference statements)
10
254
1
16
Order By: Relevance
“…The etiology of these learning difficulties is unknown. Recently, we found that stress and pain during the neonatal period are associated with alterations in HPA activation in subsequent challenges (Grunau et al, , 2005. Together with these data, our current findings begin to elucidate the complex linkages between cortisol secretion, learning, and memory in preterm infants.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The etiology of these learning difficulties is unknown. Recently, we found that stress and pain during the neonatal period are associated with alterations in HPA activation in subsequent challenges (Grunau et al, , 2005. Together with these data, our current findings begin to elucidate the complex linkages between cortisol secretion, learning, and memory in preterm infants.…”
Section: Discussionsupporting
confidence: 66%
“…Preterm infants were recruited through the Neonatal Intensive Care Unit (NICU) at the Children's and Women's Health Centre of British Columbia, Vancouver as part of an ongoing program of studies on the effects of premature birth and early pain exposure on regulatory processes and development (Grunau et al, , 2005Haley et al, 2004). As part of this larger study, chart reviews from birth to term were carried out (see Table 1).…”
Section: Participantsmentioning
confidence: 99%
“…Gestational age at birth was chosen as the grouping variable because birth weight, illness severity, gestational age and pain exposure are variables which are highly inter-correlated (e.g. Grunau et al, 2005). All analyses remained the same with the exception of the construct validity analysis; to determine whether there were differences between BIIP scores between the two groups across the three phases (Baseline, Lance/squeeze, Recovery), repeated measures analysis of variance with gestational age group as a between subjects factor was completed.…”
Section: Construct Validity: Changes In Pain Scale Scores Across Bloomentioning
confidence: 99%
“…A recent three-group study investigated long-term changes in cutaneous abdominal sensitivity in infants with pathologic abdominal disease and presumed abdominal visceral pain.l 29 1 Group 1 comprised newly born preterm and full-term neonat·es [30][31][32][33][34][35][36][37][38][39][40][41] weeks' post-conceptional age (n = 25); group 2 comprised infants with unilateral hydronephrosis (UH) 2-95 weeks' post-conceptional age (n = 30); and group 3 comprised healthy control infants 42-95 weeks' post-conceptional age (n = 52). Using nylon von Frey hairs (monoti laments of varying diameters designed to apply fixed forces to the skin).…”
Section: Neonates and Subsequent Pain Behaviorsmentioning
confidence: 99%